2014
DOI: 10.1111/bpa.12158
|View full text |Cite
|
Sign up to set email alerts
|

PDGF, Pericytes and the Pathogenesis of Idiopathic Basal Ganglia Calcification (IBGC)

Abstract: Platelet-derived growth factors (PDGFs) are important mitogens for various types of mesenchymal cells, and as such, they exert critical functions during organogenesis in mammalian embryonic and early postnatal development. Increased or ectopic PDGF activity may also cause or contribute to diseases such as cancer and tissue fibrosis. Until recently, no loss-of-function (LOF) mutations in PDGF or PDGF receptor genes were reported as causally linked to a human disease. This changed in 2013 when reports appeared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 84 publications
0
32
2
Order By: Relevance
“…The underlying pathophysiology has not been fully elucidated, but a recent neuropathology study suggests a potential role for pericytes in initiating non-dystrophic brain calcification 27. Moreover, abnormalities of pericyte function have recently been implicated in the pathogenesis of primary familial brain calcification (formerly idiopathic basal ganglia calcification; Fahr's disease) 28. Of note, the pericytes derived from human-induced pluripotent stem cells of patients with FOP show an increased ability to mineralise compared with the control group 29.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiology has not been fully elucidated, but a recent neuropathology study suggests a potential role for pericytes in initiating non-dystrophic brain calcification 27. Moreover, abnormalities of pericyte function have recently been implicated in the pathogenesis of primary familial brain calcification (formerly idiopathic basal ganglia calcification; Fahr's disease) 28. Of note, the pericytes derived from human-induced pluripotent stem cells of patients with FOP show an increased ability to mineralise compared with the control group 29.…”
Section: Discussionmentioning
confidence: 99%
“…Second, heterozygous loss‐of‐function mutations of PDGFRB [Nicolas et al, ], the gene encoding the platelet‐derived growth factor receptor β (PDGFRβ), or of PDGFB [Keller et al, ], the gene encoding its main ligand, PDGFB, are responsible for an impairment of the blood–brain barrier, a mechanism which could be involved in the development of the calcifications seen in both patients with PFBC and mouse models [Keller et al, ] (see also https://coppolalab.ucla.edu/lovd/genes where mutations in the three genes are reported). Putative links between these pathways are still under debate and deserve more investigation [Arts et al, ; Betsholtz and Keller, ]. A causative mutation within one of these genes was found in 35% of families with autosomal dominant PFBC [20%, 10%, and 5% in the SLC20A2 , PDGFB , and PDGFRB genes, respectively) in the French case series [Nicolas et al, ] while an SLC20A2 mutation was found in up to 50% of PFBC families in other studies [Hsu et al, ; Yamada et al, ] (where PDGFB and PDGFRB screening were not reported), highlighting possibly different inclusion criteria, the diagnosis of probable PFBC (with no identified genetic cause) needing the exclusion of numerous differential diagnoses [Manyam, ].…”
Section: Introductionmentioning
confidence: 99%
“…The present review focuses on SLC20A2, which harbors the highest number of causal variants and is therefore the major gene associated with PFBC [Keller et al, 2013;Nicolas et al, 2013aNicolas et al, , 2013bNicolas et al, , 2014aBetsholtz and Keller, 2014;Sanchez-Contreras et al, 2014]. Current knowledge allows us to understand several important issues concerning the SLC20A2 involvement in PFBC: (1) distribution of variants across the gene, (2) functional impact of variants linked to certain protein domains, (3) geographical distribution, and (4) a possible founder effect.…”
Section: Introductionmentioning
confidence: 99%